2016
DOI: 10.1038/nature20772
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the global phosphorus cycle

Abstract: The macronutrient phosphorus is thought to limit primary productivity in the oceans on geological timescales. Although there has been a sustained effort to reconstruct the dynamics of the phosphorus cycle over the past 3.5 billion years, it remains uncertain whether phosphorus limitation persisted throughout Earth's history and therefore whether the phosphorus cycle has consistently modulated biospheric productivity and ocean-atmosphere oxygen levels over time. Here we present a compilation of phosphorus abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
445
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 490 publications
(513 citation statements)
references
References 79 publications
33
445
2
3
Order By: Relevance
“…Reinhard and colleagues 4 argue that low P concentrations in shallow marine shales deposited throughout the majority of early Earth history reflect enhanced scavenging from anoxic, ironrich oceans, leading to severe P biolimitation. This P scarcity before approximately 800 million years ago led to increased molar C/P ratios in the biomass of primary producers, with C/P ratios of 300:1 or more, compared to the modern Redfield ratio of 106:1.…”
Section: Simon W Poultonmentioning
confidence: 99%
See 2 more Smart Citations
“…Reinhard and colleagues 4 argue that low P concentrations in shallow marine shales deposited throughout the majority of early Earth history reflect enhanced scavenging from anoxic, ironrich oceans, leading to severe P biolimitation. This P scarcity before approximately 800 million years ago led to increased molar C/P ratios in the biomass of primary producers, with C/P ratios of 300:1 or more, compared to the modern Redfield ratio of 106:1.…”
Section: Simon W Poultonmentioning
confidence: 99%
“…These processes can result in significant fluxes of P back to the water column, substantially increasing C/P ratios in the deposited sediment 9 . Reinhard and colleagues 4 implicitly include a recycling component in their model, but the extent to which the degree of recycling has evolved through time is currently poorly understood. Sulphidic marginal marine environments became more prevalent through early Earth history 1,10 as a consequence of rising sulphate concentrations in the ocean, initially in association with possible 'whiffs' of oxygen prior to Earth's first persistent rise in atmospheric oxygen, and subsequently during Earth's 'middle ages' (Fig.…”
Section: Simon W Poultonmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Reinhard et al (2017) presented a large compilation of P data from siliciclastic sediments and identified a four-fold increase in P burial at the start of the Cryogenian (~720 Ma), which they linked to progressive oxygenation of the Earth and loss of the deep-sea Fe trap. Poulton (2017) countered that the record presented by Reinhard et al (2017), and the large observed increase in P burial in the Neoproterozoic, may alternatively be explained by high P liberation and recycling from the sediment back into the water column. Accordingly, the extent to which P may have limited cyanobacterial productivity in the Proterozoic ocean remains unresolved.…”
Section: Iron Formations Primary Productivity and Atmospheric Oxygementioning
confidence: 99%
“…Although P is likely to have been the ultimate limiting nutrient (e.g., Reinhard et al, 2017), limitation need not have been restricted to this element. With denitrification in the ocean interiors, N fixation in surface waters is needed to balance any P input to the oceans.…”
Section: Iron Formations Primary Productivity and Atmospheric Oxygementioning
confidence: 99%